Faktor Yang Mempengaruhi Kebijakan Hutang - Lusiana, Sufiyati (Jurnal Paradigma Akuntansi, 2019)
The purpose of this empirical research is to obtain empirical evidence about the influence of firm’s size, asset structure, free cash flow, and institutional ownership on debt policy on manufacture companies (basic industry and chemical) listed on Indonesia’s stock exchange in 2015-2017 by using purposive sampling method for a total of 117 data in three years. The data used in this research are secondary data in form of the financial statements and performance reports. The results show that firm’s size has negative and significant effect to debt policy and asset structure has positive and significant effect to debt policy, but free cash flow and institutional ownership have not significantly effect to debt policy